Cancer in Anal Fistulas - Perez, Sean; Eisenstein, Samuel (Clinics in Colon and Rectal Surgery, 2023)
Fistula-associated anal cancer in Crohn's disease (CD) can be challenging to diagnose and treat. Patients with longstanding fistulas in the setting of CD who present with a sudden change in their symptoms should undergo biopsy under anesthesia with extensive sampling, followed by staging imaging. Pelvic magnetic resonance imaging (MRI) can be helpful in identifying the extent of the disease locally. Patients often present in the later stages due to the challenges associated with diagnosing these patients. Two subtypes of this disease include squamous cell carcinoma and adenocarcinoma, and treatment depends on diagnosis. Small sample size and lack of uniform data on treatments make it difficult to say which treatment modalities are optimal, but aggressive combined therapy is likely the best approach for survival. This will include chemotherapy and radiation and often radical resection as well. Despite this, survival is poor, although more recent data suggest that outcomes are improving.
Keywords: fistula-associate anal cancer; squamous cell carcinoma; adenocarcinoma; Crohn's disease; perianal disease